Balancing E-Commerce Platform and Manufacturer Goals in Sustainable Supply Chains: The Impact of Eco-Friendly Private Labels - Zhiheng Liu; Xiangcheng Cui; Yuanyuan Ji (Systems)
This paper analyzes how consumer preferences for eco-friendly private labels affect platform selling formats and manufacturer channel strategies. We construct a game-theoretic model that encompasses both an e-commerce platform and a manufacturer. In this model, the platform chooses its selling format—either wholesale or agency—while the manufacturer determines whether to launch an online direct channel. Our analysis takes into account consumer preferences for both product brands and sales channels. We compare and analyze the equilibrium outcomes across four different scenarios, leading to the following conclusions: (1) When the platform utilizes the wholesale selling format, the manufacturer is consistently motivated to launch the direct channel if the costs associated with it are low. Conversely, when the platform employs the agency selling format, the manufacturer’s decision to establish an online direct marketing channel depends on the relative strength of consumers’ eco-friendly and channel preferences. (2) The platform’s choice of selling format is affected by the manufacturer’s channel strategy, leading the platform to modify its selling format based on varying manufacturer channel approaches. (3) The choices of the platform’s selling format and the manufacturer’s channel strategy are not always in conflict. When consumer preferences for the manufacturer’s direct channel are strong and the cost of introducing it is moderate, the platform’s decision to adopt the agency selling format can create a win-win outcome for both the platform and the manufacturer. And the establishment of online channels by manufacturers further enhances the sustainable growth of eco-friendly products.